Relationships between developmental strategies for additional indications and price revisions for anticancer drugs in Japan - Hideki Maeda; Ayano Okabe; Kenichi Sakakura; Daniel Bin Ng; Manabu Akazawa (BMC, 2021)
Abstract Background The relationships between developmental strategies for additional indications and drug price revisions have not been thoroughly studied. Here, we investigated the price revisions for anticancer drugs approved in Japan. Methods The study was based on published information on anticancer drugs approved between January 2009 and March 2020 in Japan. We investigated the relationships between the pharmacological and regulatory characteristics of anticancer drugs and occurrence/non-occurrence of the Japanese National Health Insurance (NHI) price revisions. Results Eighty-one new anticancer drugs were given NHI price listings during the survey. On April 1, 2020, the prices of 23 anticancer drugs had been revised from the initial pricing, the prices were reduced for 21 drugs (91.3%). Several parameters showed the relationships between drug characteristics and NHI price revisions. The achievement of additional indications and compound type were identified as explanatory factors for these relationships. Additional indication profiles were defined to assess the relationships between the methods for additional indication achievement and price revisions. When the type of additional indication was "Expansion", the percentage of drugs received NHI price revisions was the highest (P<0.001). Conclusions NHI price revision was significantly related to the achievement of additional indications and compound type. The strategy for additional indications was found to affect the occurrence/non-occurrence of NHI price revisions.